Lezbične in gejevske družine v Sloveniji - Urek, Mojca (Družboslovne razprave, 2005)
Social science literature usually classifies lesbian and gay families among nontraditional, unconventional or alternative families. In the first part of the article the author draws attention to the inappropriate classification involved with such families. By using adjectives such as non-traditional, unconventional etc., we in fact emphasize the difference and deviation from normality that both automatically become the object of predomination. However, within such contexts "special" family forms become separated, inferior and unequal as proves the public discourse, which is infused with prejudice and the so-called concern of professional and laic public that discusses the consequences, children might endure growing up in such families. The author analyses the public institution's discourse concerning lesbian and gay families by critically observing the main arguments introduced by different experts that the politics uses in order to contradict the legalisation of same-sex parenthood. Further on, the author examines the family support the children, mothers and fathers are given in such families, especially from the point of view of the social work. The author concludes that much potential and tasks are to be performed by social work in the context of contemporary changes in family life, especially in relation to lesbian and gay families.
Keywords: Slovenia; Slovenija; družina; family; istospolne skupnosti; otroci; child; socialno delo; social work; socialna pomoč